Pedagogická praxe studentů učitelství biologie z pohledu mentorských rozhovorů - Němečková, Linda; Pavlasová, Lenka (Scientia in educatione, 2020)
Pedagogical practice is an important part of a future teacher´s training and the mentor interviews between the student teacher and the mentor play a key role during this practice. The article describes an analysis of mentor interviews by student teachers of biology. These were conducted in order to find out which aspects of teaching the student teachers are dealing with, which they omit, and which may cause them difficulties. We focused on subject-specific phenomena in biology lessons in five areas: teaching objectives, extent and content, the procedure of working with teaching materials / aids, student teachers´ and pupils´ mistakes, and the popularity of topics and motivation. The respondents of the research were student teachers of biology (n = 35), who were in their follow-up master's degree program, completing their pedagogical practice at either low or upper secondary schools. Most often the student teachers set only cognitive objectives which were formulated primarily using the content of the curriculum. Key competences and active verbs were used in a limited extent in their objectives. The extent of the curriculum was most often determined by the teacher or habits of the school, while presented organisms were most often determined by the textbook. A large number of respondents were able to mention the specific mistakes they made in the classroom, but with one exception: the respondents did not comment on the pupils' mistakes. The most common way of motivating pupils was using illustrations with various teaching aids. We believe that the results can contribute to improving the preparation of biology student teachers, especially in the field of mentoring interviews in continuous teaching practice.